2019
DOI: 10.1177/0040517519886636
|View full text |Cite
|
Sign up to set email alerts
|

Producing light-weight bast fibers from canola biomass for technical textiles

Abstract: Due to the excessive use of water required for cotton cultivation, scientists in this field have been looking at waste biomass as an alternative source of fiber supply. Canola waste biomass is a source of textile fibers which effectively costs nothing, as the biomass can be collected from the waste plant stems of canola plants after harvesting. Therefore, an investigation has been conducted to identify the characteristics of canola fiber and of the canola cultivar ( Brassica napus L.) suitable for textile appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 18 publications
4
46
0
Order By: Relevance
“…Khan (2016) conducted a separate research work and found the fibre yield (%) of 20 different Canola cultivars (excluding 5440, 45H29) ranged between 6.23 and 13.82%; the fibre yield (%) of HYHEAR 1 was 12.66% and for Topas 10.63%. Fibre yield (%) found by Shuvo et al (2019) was within this range reported by Khan (2016). Regarding moisture regain (%) (MR), HYHEAR 1 showed the highest (12.53 ± 3.37%) MR and 45H29 showed the least (9.31 ± 3.40%) among the water-retted virgin canola fibres (Shuvo, 2019), whereas HYHEAR 1 showed the highest (7.64 ± 0.03%) MR and Topas showed the least (6.03 ± 0.05%) among the 10% softener-treated canola fibres.…”
Section: Influence Of Different Cultivars Of Industrial Crops On Textsupporting
confidence: 87%
See 4 more Smart Citations
“…Khan (2016) conducted a separate research work and found the fibre yield (%) of 20 different Canola cultivars (excluding 5440, 45H29) ranged between 6.23 and 13.82%; the fibre yield (%) of HYHEAR 1 was 12.66% and for Topas 10.63%. Fibre yield (%) found by Shuvo et al (2019) was within this range reported by Khan (2016). Regarding moisture regain (%) (MR), HYHEAR 1 showed the highest (12.53 ± 3.37%) MR and 45H29 showed the least (9.31 ± 3.40%) among the water-retted virgin canola fibres (Shuvo, 2019), whereas HYHEAR 1 showed the highest (7.64 ± 0.03%) MR and Topas showed the least (6.03 ± 0.05%) among the 10% softener-treated canola fibres.…”
Section: Influence Of Different Cultivars Of Industrial Crops On Textsupporting
confidence: 87%
“…Whereas, pectin was completely removed from hemp fibre interior by the NaOH boiling process, lignin was not completely removed, as a small portion of lignin was situated in the second wall layers of the fibres which cannot be accessed by NaOH. Similarly, an alkaline and acidic bath treatment followed by a softener treatment also produced textile grade canola fibres (Shuvo et al 2019) to achieve the optimum result for CSP of canola fibres, whereas Sevenhuysen and Rahman (2016) used an enzymatic treatment to produce textile grade canola fibres.…”
Section: Chemical Composition Of Natural Lignocellulosic Fibres and Tmentioning
confidence: 99%
See 3 more Smart Citations